Forms of vitamin B12 in radioisotope dilution assays. - Begley, J A (1981)
Since the presence of analogues of vitamin B12 (B12, cobalamin, Cbl) has been postulated as the basis for the high values obtained by some radioisotope dilution assays (RIDA) of serum Cbl we examined serum for analogues. None could be demonstrated in the extracts of serum prepared for RIDA as sought by both direct and indirect techniques. The natural forms of serum Cbl were converted to cyanocobalamin (CN Cbl) by this process of extraction which included cyanide (CN). The correctly performed RIDA for Cbl based on R binder gave higher values than a RIDA based on intrinsic factor or than by bioassay. By exclusion, the difference appeared to be due to unidentified factors rather than the presence of analogues.